Modified method for evaluating improved technologies for indoor thermal environment of earth buildings. (15th October 2018) - Zhang, Jing; Xu, Wei; Li, Angui; Zheng, Kun; Zhang, Jinping
Abstract: About 30% of the global population lives in earth buildings. To meet the needs of modern life, improved technologies have been used in such buildings. But, how well does that work? Unfortunately, such evaluation are lacking. So, this study focused on developing a comprehensive evaluation method. First, 19 improvement schemes were proposed based on field tests of an adobe dwelling in Gansu, China. Then, a modified method to evaluate the improvement technologies was proposed. The comprehensive evaluation addressed four constraints – ecology, economy, energy savings, and thermal comfort – with six indexes. Furthermore, two real-world problems were solved. One was the subjectivity of index weight, and the other was the target value fluctuating within a certain range. Finally, an analysis and comparison of each scheme between four isolated evaluations and a comprehensive integrated evaluation were carried out. The results indicated that comprehensive evaluation was superior and that the grey interval relational decision algorithm (GIRDA) can effectively evaluate improved technologies. Furthermore, it was recommended that, when capital is limited, insulating roofs with rice husk is the best choice. These results are intended to provide guidance for improving the standard of living in poor rural areas in China. Highlights: Grey Interval Relational Decision is used to evaluate passive technology for indoor thermal environment of earth dwellings. Entropy weight analysis is used to calculate index weights to solve the problem of unknown or subjective of index weight. Interval grey number solves the other realistic problem, which is the target value be of numerical interval. A comprehensive evaluation of schemes from four aspects was carried out. The whole process of the algorithm is demonstrated by examples.